The Relation of Teacher Ratings of Attention and Executive Functioning to Reading Comprehension - Poole, Tara; Harrison, Gina (Exceptionality Education International, 2026)
In this study, we examined the associations between teacher-rated symptoms of attention-deficit/hyperactivity disorder (ADHD) and executive functioning (EF) to reading comprehension. Young children with ADHD and deficits in EF are at greater risk for academic underachievement, including reading comprehension difficulties. Less is known about the association between EF, ADHD symptoms, and the reading subskills outlined in the simple view of reading (SVR) that are required for reading comprehension. Using a cross-sectional, descriptive correlational research design, we gathered data virtually on 27 elementary students from one school at the start of the COVID-19 pandemic. Standardized assessment measures capturing reading-related skills, EF, and ADHD symptoms were used. Data underwent correlation and hierarchical regression analyses to investigate the relations between EF, ADHD symptoms, reading comprehension, and reading comprehension subskills outlined in the SVR. Word reading and language skills were positively associated with reading comprehension performance, and word reading ability significantly predicted reading comprehension. Teacher ratings of EF deficits were negatively associated with reading comprehension and decoding, while language comprehension and teacher ratings of EF and ADHD symptoms explained a small amount of variance in reading comprehension performance. These findings highlight the need for further research examining the role that EF plays in reading comprehension and related skills to inform future reading interventions for students with EF deficits and heightened ADHD symptoms.